Optimalisasi Penjualan Keukarah melalui Desain Berbasis di Desa Keude Siblah - Irawan, Azmida; Cui, Yus Erni; Alfa, Raudhatul (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This community engagement program aimed to enhance the skills of PKK microbusiness members in Keude Siblah Village by using AI-based design technology to promote local products, especially the traditional Keukarah cake. Despite its cultural and economic value, Keukarah faces challenges in digital marketing. The program involved 15 participants and was carried out through Canva AI training. Activities included initial observation, program introduction, visual design training, promotional material assistance, and final evaluation. Each participant produced two promotional designs: a poster and a digital flyer. The results showed an improved ability to independently create packaging and visual materials, along with increased use of social media for product promotion. The program also raised awareness of the importance of branding and digital marketing. It successfully empowered participants to adapt to technology using a simple and practical approach. Similar initiatives are recommended to support the growth of digital microbusinesses at the village level.